Thermoluminescent response of silica beads to high-dose irradiations. (February 2020) - Ley, K.; Hashim, S.A.; Lohstroh, A.; Shenton-Taylor, C.; Bradley, D.A.
Abstract: Glow-curves obtained using a Ris ø TL/OSL reader, have been studied for 10 different coloured bead types from the manufacturer Toho, Japan, after irradiation using a 1 MeV electron beam at the Alurtron Irradiation Facility, Malaysia Nuclear Agency, giving doses up to 250 kGy. For doses larger than and including 5 kGy, it can be observed by eye that the beads darken with increasing dose. The beads almost return to their original appearance after being read out and annealed at 400 °C, showing the potential for a colour changing dosimeter that is reusable and chemically inert. Beads showing the highest TL response are the Frosted and Pink colours which show evidence of a possible maximum Mass Normalised TL Response as a function of dose in the range of 40 kGy–50 kGy. Data fitting was achieved using weighted fits of second order exponentials and linear fits for different data sets, with calculated p-values ≪ 0.05 for almost all coefficients obtained. Topaz, Red and Lilac coloured beads show a plateau in the TL response as a function of dose, where as the Blue and Yellow beads show a correlation similar to that of the Pink, Frosted and Rose beads with an estimated maximum in Mass Normalised TL Response of 100 kGy. Highlights: TL response measured for electron beam irradiation of 1 kGy–250 kGy, for 10 colours of beads. All beads visibly change colour for doses ≥ 5 kGy, except Lilac. Greatest TL produced from Pink and Frosted beads, Green and Lime beads generally show low yields. Plateau observed for TL Response as function of Dose for Red, Topaz and Lilac beads. Remaining beads show initial increase then linear decrease of TL response with increasing dose.